Voluntary commitments lead to efficiency - Adam Tauman Kalai; Ehud Kalai; Ehud Lehrer; Dov Samet (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
Real world players often increase their payoþs by voluntarily committing to play a .xed strategy, prior to the start of a strategic game. In fact, the players may further bene.t from commitments that are conditional on the commitments of others. This paper proposes a model of conditional commitments that uni.es earlier models while avoiding circularities that often arise in such models. A commitment folk theorem shows that the potential of voluntary conditional commitments is essentially unlimited. All feasible and individually rational payoþs of a two-person strategic game can be attained at the equilibria of one (universal) commitment game that uses simple commitment devices. The commitments are voluntary in the sense that each player maintains the option of playing the game without commitment, as originally de.ned
Keywords: 330; Spieltheorie; Folk-Theorem; Kooperatives Spiel